Türkiye Funası için Yeni Bir Kayıt (Coleoptera: Hydrophilidae) ve Laccobius sinuatus Motschulsky, 1849 ile Coelostoma transcaspicum Reitter, 1906 Üzerine İlave Notlar - İncekara, Ümit; Bektaş, Mehmet; Taşar, Gani Erhan; Polat, Ahmet (Fırat University, 2016)
Hidrofilidlerden Türkiye faunası için yeni kayıt olan Helochares sharpi Kuwert, 1890 sunuldu. Laccobius siniatus Motschulsky, 1849'un Türkiye’deki dağılışı doğrulandı. Coelostoma transcaspicum Reitter, 1906 Türkiye’den ikinci defa kaydedildi. Genel deskripsiyon, dağılım bilgileri ve bu türlere ait aedeagofor fotoğrafları birlikte sunuldu.

A new record of hydrophilid beetle, Helochares sharpi Kuwert, 1890 is presented. Distribution of Laccobius siniatus Motschulsky, 1849 in Turkey was confirmed. However, Coelostoma transcaspicum Reitter, 1906 was recorded secondly from Turkey. General description, distributional data and photos of its aedeagophores have also been presented.
A New Record for The Turkish Fauna (Coleoptera: Hydrophilidae), with Further Notes on The Laccobius Sinuatus Motschulsky, 1849 and Coelostoma Transcaspicum Reitter, 1906
Keywords: Engineering; Mühendislik